New cyclotetrapeptides and a new diketopiperzine derivative from the marine sponge-associated fungus Neosartorya glabra KUFA 0702 - Zin W.W.M. (2016)
Two new cyclotetrapeptides, sartoryglabramides A (5) and B (6), and a new analog of fellutanine A (8) were isolated, together with six known compounds including ergosta-4, 6, 8 (14), 22-tetraen-3-one, ergosterol 5, 8-endoperoxide, helvolic acid, aszonalenin (1), (3R)-3-(1H-indol-3-ylmethyl)-3,4-dihydro-1H-1,4-benzodiazepine-2,5-dione (2), takakiamide (3), (11aR)-2,3-dihydro-1H-pyrrolo[2,1-c][1,4]benzodiazepine-5,11(10H,11aH)-dione (4), and fellutanine A (7), from the ethyl acetate extract of the culture of the marine sponge-associated fungus Neosartorya glabra KUFA 0702. The structures of the new compounds were established based on extensive 1D and 2D spectral analysis. X-ray analysis was also used to confirm the relative configuration of the amino acid constituents of sartoryglabramide A (5), and the absolute stereochemistry of the amino acid constituents of sartoryglabramide A (5) and sartoryglabramides B (6) was determined by chiral HPLC analysis of their hydrolysates by co-injection with the D- and L- amino acids standards. Compounds 1-8 were tested for their antibacterial activity against Gram-positive (Escherichia coli ATCC 25922) and Gram-negative (Staphyllococus aureus ATCC 25923) bacteria, as well as for their antifungal activity against filamentous (Aspergillus fumigatus ATCC 46645), dermatophyte (Trichophyton rubrum ATCC FF5) and yeast (Candida albicans ATCC 10231). None of the tested compounds exhibited either antibacterial (MIC > 256 μg/mL) or antifungal activities (MIC > 512 μg/mL). © 2016 by the authors; licensee MDPI.